An Analytical-Comparative Study of Lurish and Kurdish Mourning Rituals and the Mourning Tradition in Shahnameh - Najmedin gilani; Morteza Akbari; Siavash Yari (ادبیات تطبیقی, 2018)
The tradition of mourning for the dead is an ancient tradition. It is one of the long-lasting rituals, which was not forgotten or abolished, but increased in importance and prominence, as a result of altruism, men’s gratitude and appreciation towards their relative and martyrs. Especially, the death of heroes, noblemen, and martyrs in the way of defending their homelands has never been erased from the minds of men. The Kurds and the Lurs, as two of the Iranian ethnic groups, have always well kept and preserved many ancient traditions over the course of history. For example, they perform mourning rituals for the noblemen and heroes as they were in ancient Iran and in Ferdowsi’s Shahnameh.  So that, the Lurish and Kurdish inhabited regions follow some similar mourning rituals in Shahnameh, such as the period of mourning, wearing black clothes, scratching the face, pulling on the hair, throwing dust over the head, mourning songs, etc. This study tries to compare Lurish and Kurdish mourning rituals with the mourning tradition in Shahnameh, using references and descriptive-analytical method.